Optimization of asymmetric bioreduction conditions of 1-indanone by Leuconostoc mesenteroides N6 using a face-centered design-based multi-objective optimization model - Alamoudi, Mohammed; Ozdemir, Akin; Dertli, Enes; Bolubaid, Mohammed; Alidrisi, Hassan M.; Taylan, Osman; Yilmaz, Mustafa Tahsin; Sahin, Engin (TAYLOR & FRANCIS INC, 2024)
There has been an increasing interest in biocatalysts over the past few decades in order to obtain high efficiency, high yield, and environmentally benign procedures aiming at the manufacture of pharmacologically relevant chemicals. Lactic Acid Bacteria (LAB), a microbial group, can be employed as biocatalysts while performing asymmetric reduction of prochiral ketones. In this study, Leuconostoc mesenteroides N6 was used for the asymmetric bioreduction 1-indanone. And then, a novel and innovative face-centered design-based multi-objective optimization model was used to optimize experimental conditions. Also, the experimental design factors were defined as agitation speed, incubation period, pH, and temperature for optimization to acquire the maximum enantiomeric excess (ee) and conversion rate (cr) values. When using the face-centered design-based multi-objective optimization model, the optimum culture conditions corresponded to 96.34 and 99.42%, ee and cr responses, respectively, were pH = 5.87, incubation temperature = 35 degrees C, incubation period = 50.88 h, and agitation speed = 152.60 rpm. Notably, the validation experiment under the optimum model conditions confirmed the model results. This study demonstrated the importance of the optimization and the efficiency of the face-centered design-based multi-objective model.
Keywords: Bioreduction; lactic acid bacteria; Leuconostoc mesenteroides N6; optimization; (S)-1-indanol; BIOCATALYSIS; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology